Properties of Bituminous Binder Modified with High Density Polyethylene - Kalantar, Z.; Mahrez, A.; Karim, M.R. (2009)
The purpose of this research is to investigate the possibility of using High Density Polyethylene as polymer additives in Bituminous Mix. The characteristics of HDPE-modified binder obtained by fix mixing time and fix mixing temperature. was investigated. The binders were prepared by mixing the HDPE in 0.5%, 1%, 2% and 4% (by the weight of optimum bitumen) with 80/100 penetration grade bitumen at temperature of 180 ºC and 60 min of mixing time. It may be inferred that HDPE-modified bituminous binders provide better resistance against permanent deformations due to their higher complex shear modulus and lower phase angle as compared to conventional binder. It also contributes to recirculation of plastic wastes as well as to the protection of the environment.